Analysis of HIV-1 protease gene reveals frequent multiple infections followed by recombination among drug treated individuals living in São Paulo and Santos, Brazil. - Edsel Renata De Morais Nunes (Public Library of Science (PLoS), 2014)
The present study investigated the prevalence of HIV-1 multiple infections in a population composed by 47 patients under HAART failure and enrolled at the National DST/AIDS, Program, Ministry of Health, Brazil.Detection of multiple infections was done using a previously published RFLP assay for the HIV-1 protease gene, which is able of distinguishing between infections caused by a single or multiple HIV-1 subtypes. Samples with multiple infections were cloned, and sequence data submitted to phylogenetic analysis. We were able to identify 17 HIV-1 multiple infections out of 47 samples. Multiple infections were mostly composed by a mixture of recombinant viruses (94%), with only one case in which protease gene pure subtypes B and F were recovered. This is the first study that reports the prevalence of multiple infections and intersubtype recombinants in a population undergoing HAART in Brazil. Based on the data there was a steep increase of multiple infections after the introduction of the combined antiretroviral therapy in Brazil. Cases of multiple infections may be associated with HIV-1 genetic diversity through recombination allowing for the generation of viruses showing a combination of resistance mutations.